Co-pyrolysis mechanism of seaweed polysaccharides and cellulose based on macroscopic experiments and molecular simulations. (March 2017) - Wang, Shuang; Xia, Zhen; Hu, Yamin; He, Zhixia; Uzoejinwa, Benjamin Bernard; Wang, Qian; Cao, Bin; Xu, Shanna
Highlights: Co-pyrolysis conversion of seaweed polysaccharides and cellulose were investigated. The main pyrolysis products of green and brown algal polysaccharides are different. Synergistic effects were studied using the molecular dynamics simulation method. The results of simulation were consistent with the experimental results. Synergy was found during the co-pyrolysis of seaweed polysaccharides and cellulose. Abstract: Co-pyrolysis conversion of seaweed ( Enteromorpha clathrat and Sargassum fusiforme ) polysaccharides and cellulose has been investigated. From the Py-GC/MS results, Enteromorpha clathrata (EN) polysaccharides pyrolysis mainly forms furans; while the products of Sargassum fusiforme (SA) polysaccharides pyrolysis are mainly acid esters. The formation mechanisms of H2 O, CO2, and SO2 during the pyrolysis of seaweed polysaccharides were analyzed using the thermogravimetric-mass spectrometry. Meanwhile the pyrolysis of seaweed polysaccharide based on the Amber and the ReaxFF force fields, has also been proposed and simulated respectively. The simulation results coincided with the experimental results. During the fast pyrolysis, strong synergistic effects among cellulose and seaweed polysaccharide molecules have been simulated. By comparing the experimental and simulation value, it has been found that co-pyrolysis could increase the number of molecular fragments, increase the pyrolysis conversion rate, and increase gas production rate at the middle temperature range.